GROWTH PERFORMANCE AND SERUM BIOCHEMICAL PROFILE OF CROSSBRED (LWY X DESI) ENTIRE MALE PIGS FED SHEANUT CAKE DIETS - D. Sudeesh; J. Suresh; A. Ravi; S.Sreedhar; J.V. Ramana (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was undertaken on 24 crossbred pigs to study the effect of different levels of sheanut cake (SNC) by replacing deoiled rice bran (DORB) (T1-0%, T2-50%, T3-75% and T4-100%) on growth performance and serum biochemical profile of crossbred (Large White Yorkshire X Desi) entire male pigs. There was a significant (P